2018
DOI: 10.1039/c8ob01767k
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationship of novel low-generation dendrimers for gene delivery

Abstract: Structure-activity relationship (SAR) studies are very critical to design ideal gene vectors for gene delivery. However, It is difficult to obtain SAR information of low-generation dendrimers due to the lack of easy structural modification ways. Here, we synthesized a novel family of rigid aromatic backbone-based low-generation polyamidoamine (PAMAM) dendrimers. According to the number of primary amines, they were divided into two types: four-amine-containing PAMAM (DL1-DL5) and eight-amine-containing PAMAM (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Furthermore, PAMAM G4 dendrimers, both cationic and neutral, seem to be internalized by a caveolin-and clathrin-independent pathway in human lung carcinoma A549 cells [53] while low generation (G2) amine-terminated dendrimers are also taken up mainly by CME pathway in human colon adenocarcinoma Caco-2 cells [54] and by CME and CVME in HEK293 human embryonic kidney epithelial cells [53]. On the other hand, anionic, -COOH and -OH terminated dendrimers, are taken up by CVME [41] even though some researchers suggest that CME could also play a role [55].…”
Section: Dendrimersmentioning
confidence: 99%
“…Furthermore, PAMAM G4 dendrimers, both cationic and neutral, seem to be internalized by a caveolin-and clathrin-independent pathway in human lung carcinoma A549 cells [53] while low generation (G2) amine-terminated dendrimers are also taken up mainly by CME pathway in human colon adenocarcinoma Caco-2 cells [54] and by CME and CVME in HEK293 human embryonic kidney epithelial cells [53]. On the other hand, anionic, -COOH and -OH terminated dendrimers, are taken up by CVME [41] even though some researchers suggest that CME could also play a role [55].…”
Section: Dendrimersmentioning
confidence: 99%
“…Dendrimers are nanoparticles characterized by long, branched polymer chains and are readily customizable in terms of their molecular architecture, which confers the ability to carry a wider variety of drugs and allows surface functionalization, for example for conjugating permeation or targeting moieties ( Kheiriabad et al, 2021 ). One study demonstrated greater gene transfection efficiency of a polyamidoamine dendrimer over the commercially available transfection reagent, Lipofectamine 2000, a lipid nanoparticle ( Gao et al, 2018b ). Another polyamindoamine-based dendrimer was used to deliver an ATOH1 -containing plasmid to the rat inner ear.…”
Section: Novel Drug Delivery Systemsmentioning
confidence: 99%
“…Further, Gao et al studied structure activity relationship to design efficient gene delivery vectors. They demonstrated that both hydrophobic modification and density of amines modulate the gene transfer ability of synthetic vectors (Gao et al, 2018).…”
Section: Synthetic Polymersmentioning
confidence: 99%